The Impact of Mobile Internet Adoption by Cocoa Farmers: A Case Study in Southern East Java, Indonesia - Nabhani, Irfan; Daryanto, Arief; Machfud, Machfud; Rifin, Amzul (Universitas Prasetiya Mulya, 2015)
The objective of this paper is to examine the impact of mobile internet adoption by cocoa farmers into their business performance. The main factors examined in this study are creativity and innovativeness. The study sample consists of 193cocoa farmers with 24% smart phone penetrationin thirteen cocoa farmer centers in southern East Java. Data were analyzed by employing Structural Equation Modeling (SEM). The findings revealed that the business performance is significantly impacted by creativity and innovativeness. Creativity and innovativeness was measured by new product development, new process, and new marketing way; while business performance was measured by sales increase, profitability improvement and market share. This research has a limitation that the generalizability of the findings is limited to the geographical scope of the sample. Based on findings, as the practical implications of this study, to give a meaningful broadband to the farmers, all stake holders need to build a conducive broadband ecosystem for the farmer by providing better access to device, user friendly applications, and better broadband customer experience.